2007
DOI: 10.1002/ejic.200700078
|View full text |Cite|
|
Sign up to set email alerts
|

NMR Studies of Paramagnetic Metallocarbaporphyrinoids

Abstract: Carbaporphyrinoids provide a suitable macrocyclic platform for organometallic investigations that provide unique opportunities for modifying a macrocyclic structure. Alteration of a coordination core is a route of choice for stabilizing unusual metal ion oxidation states and coordination geometries. This microreview presents the general characteristic of paramagnetic metallocarbaporphyrinoids, with a focus on NMR studies. NMR spectroscopy of paramagnetic molecules can be considered as a powerful probe of sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 110 publications
0
17
0
Order By: Relevance
“…1 H NMR spectroscopy was shown to be a uniquely definitive method for detecting and characterizing paramagnetic metalloporphyrinoids and can be applied as a definitive probe for detecting metal–arene interaction in benziporphyrins. ,, It was shown that, depending on axial ligation, the one-electron oxidation of ruthenium porphyrins afforded ruthenium­(II) porphyrin π-cation radicals or ruthenium­(III) porphyrins. , In the second case, two fundamental (d xy ) 2 (d xz d yz ) 3 or less-common (d xy ) 1 (d xz d yz ) 4 electronic structures are possible, distinguished by the distribution of an unpaired electron on d orbitals to be directly correlated with the diagnostic pattern of paramagnetically shifted 1 H NMR resonances.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 H NMR spectroscopy was shown to be a uniquely definitive method for detecting and characterizing paramagnetic metalloporphyrinoids and can be applied as a definitive probe for detecting metal–arene interaction in benziporphyrins. ,, It was shown that, depending on axial ligation, the one-electron oxidation of ruthenium porphyrins afforded ruthenium­(II) porphyrin π-cation radicals or ruthenium­(III) porphyrins. , In the second case, two fundamental (d xy ) 2 (d xz d yz ) 3 or less-common (d xy ) 1 (d xz d yz ) 4 electronic structures are possible, distinguished by the distribution of an unpaired electron on d orbitals to be directly correlated with the diagnostic pattern of paramagnetically shifted 1 H NMR resonances.…”
Section: Resultsmentioning
confidence: 99%
“…One has to be aware of the fact that the organometallic chemistry of paramagnetic metallocarbaporphyrinoids has been focused on a rather limited number of transition-metal ions [copper­(II), iron­(II,III), and nickel­(I,II)]. The selected ligands such as N-confused porphyrin, O-confused porphyrin, m -benziporphyrin, N-confused pyriporphyrin, vacataporphyrin, ethyneporphyrin, and p -benziporphyrin provided the appropriate macrocyclic environment. ,, …”
Section: Introductionmentioning
confidence: 99%
“…N-Confused pyriporphyrin 472b afforded an iron­(II) complex 476 , and this reacted with molecular oxygen to give an oxygen-bridged iron­(III) complex 477 (Scheme ). , …”
Section: Benziporphyrins Heterobenziporphyrins and Related Systemsmentioning
confidence: 99%
“…Since brief reviews on porphyrin analogues including NCPs and expanded porphyrins are already reported, this review especially focuses on the recent development in the chemistry of NCP, NFP and related compounds. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] The evolutionary tree of the porphyrin family relevant to confusion is summarized in Chart 1. Although carbaporphyrins, heteroporphyrins and hetero-confused porphyrins are obviously important and interesting members of the porphyrin family, they are not mentioned here because of space considerations.…”
Section: Introductionmentioning
confidence: 99%